An Early Arabic Translation of Exodus 15 from a Palestinian Melkite Psalter in the Cairo Genizah - Posegay, Nick (Collectanea Christiana orientalia, 2024)
This article presents an Arabic translation of Exodus 15 from the Cairo Genizah, preserved in two fragments of a Christian lectionary (MSS CUL T-S NS 305.198 and T-S NS 305.210). The style of the lectionary's Arabic script suggests that it was copied by a well-trained scribe in the late 9th or early 10th century. Such a date makes it the oldest Christian Arabic Bible translation yet found in the Genizah. Linguistic analysis further indicates that its translator had access to the Peshitta and either the Syro-Hexapla or Septuagint of Exodus 15 during their work. Most likely, this translator was a ninth-century Melkite Christian who spoke both Syriac and Arabic.